2021
DOI: 10.1101/2021.06.26.450057
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Markovian Weighted Ensemble Milestoning (M-WEM): Long-time Kinetics from Short Trajectories

Abstract: We introduce a rare-event sampling scheme, named Markovian Weighted Ensemble Milestoning (M-WEM), which inlays the weighted ensemble framework within a Markovian milestoning theory to efficiently calculate thermodynamic and kinetic properties of long-timescale biomolecular processes from short atomistic molecular dynamics simulations. We then showcase the application of this method to the Muller Brown potential model, the conformational switching in alanine dipeptide, and the millisecond timescale protein-liga… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 119 publications
0
1
0
Order By: Relevance
“…OneOPES Light OneOPES A more arduous test is the ligand-binding benchmark Trypsin-Benzamidine. While this system has been routinely used for years as a benchmark for ligand-binding methods 61,[63][64][65][66][67][68][69][70][71][72][73] , it is far from trivial and still offers a significant challenge. High-resolution crystallographic experiments have recently demonstrated that individual water molecules play a crucial role in the system's binding/unbinding process 74 , so that the introduction of specialised water-focused CVs proved decisive in bringing simulations to convergence in our recent work 56 .…”
Section: Trypsin-benzamidinementioning
confidence: 99%
“…OneOPES Light OneOPES A more arduous test is the ligand-binding benchmark Trypsin-Benzamidine. While this system has been routinely used for years as a benchmark for ligand-binding methods 61,[63][64][65][66][67][68][69][70][71][72][73] , it is far from trivial and still offers a significant challenge. High-resolution crystallographic experiments have recently demonstrated that individual water molecules play a crucial role in the system's binding/unbinding process 74 , so that the introduction of specialised water-focused CVs proved decisive in bringing simulations to convergence in our recent work 56 .…”
Section: Trypsin-benzamidinementioning
confidence: 99%